From Radical Autonomy to Divine Trust: Rethinking Human Freedom through Sartre and Tawhid - Furqan, Fatik; Juwaini, Juwaini; Huringin, Nabila; Yasin, Taslim HM. (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2025)
This article critically examines the concept of human freedom through a comparative analysis of Jean-Paul Sartre’s existentialism and the Islamic doctrine of tawhid. Employing a qualitative library research method, the study analyzes Sartre’s foundational texts—Being and Nothingness and Existentialism is a Humanism—alongside key Islamic philosophical and theological sources. Sartre views human freedom as absolute and burdened with self-definition in the absence of divine authority, leading to anxiety, alienation, and moral subjectivism. In contrast, Islam situates freedom within the framework of divine will (qada’ and qadar), viewing it as a trust (amanah) exercised under God’s guidance and evaluated through moral accountability. Through four key themes—ontological freedom, responsibility, divine will, and moral implication—the study demonstrates that while Sartre articulates the existential depth of human autonomy, the Islamic worldview offers a more coherent and ethically sustainable model of freedom. This integrated understanding grounds freedom in spiritual purpose, communal responsibility, and the moral agency of the individual. Abstrak: Artikel ini mengkaji tentang konsep kebebasan manusia melalui analisis perbandingan antara eksistensialisme Jean-Paul Sartre dan doktrin tawhid dalam Islam. Dengan menggunakan metode penelitian kualitatif berbasis studi pustaka, kajian ini menganalisis teks-teks utama Sartre—Being and Nothingness dan Existentialism is a Humanism—bersama sumber-sumber filsafat dan teologi Islam klasik maupun kontemporer. Sartre memandang kebebasan manusia sebagai sesuatu yang absolut dan menuntut definisi diri sepenuhnya dalam ketiadaan otoritas ilahi, yang pada akhirnya melahirkan kecemasan, keterasingan, dan moralitas yang subjektif. Sebaliknya, Islam menempatkan kebebasan dalam kerangka kehendak ilahi (qada’ dan qadar), sebagai amanah yang dijalankan di bawah bimbingan Tuhan dan dipertanggungjawabkan secara moral. Melalui empat tema utama—ontologi kebebasan, tanggung jawab, kehendak Tuhan, dan implikasi moral—studi ini menunjukkan bahwa meskipun Sartre berhasil mengartikulasikan kedalaman eksistensial dari kebebasan manusia, pandangan Islam menawarkan model kebebasan yang lebih koheren dan berkelanjutan secara etis. Pemahaman yang terintegrasi ini menempatkan kebebasan dalam tujuan spiritual, tanggung jawab sosial, dan agensi moral individu.